The Meaning of Ezekiel 44,6-14 in Light of Ezekiel 1-39 - Kilchör, Benjamin 1984- (2017)
This paper argues that the primary referent of Ezek 44,6-14 is located in the former chapters of the Book of Ezekiel (esp. Ezekiel 8) rather than in historical events or biblical texts outside of the book of Ezekiel. On this reading, Ezek 44,6-14 not only refers to Ezekiel 8 in a direct way, but it also takes into account the interpretations that Ezekiel 8 has received in Ezek 14,1-11 (the house of Israel went astray), Ezek 16,58-63 (the abominations broke God’s covenant with Israel), and Ezek 23,38-42 (the defilement of the sanctuary has to do with foreigners).
Keywords: Ezechiel -- Prophet; Bibel